Pengaruh Kompensasi Dan Keseimbangan Kerja Terhadap Kinerja Karyawan PT. New Living Indonesia Tangerang Banten - Wafa Altamira; I Made Aryata (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine how the influence of compensation and work balance on employee performance at PT New Living Indonesia Tangerang Banten both partially and simultaneously. The method used in this study is a quantitative descriptive method. The sampling technique used is a saturated sample technique with a sample of 82 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, descriptive analysis, simple regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study are compensation has a positive effect on employee performance with a regression equation value of Y = 17,195 + 0.610 X1, a correlation coefficient of 0.642 meaning that the two variables have a strong level of relationship. The determination value is 41.3% while the remaining 58.7% is influenced by other factors. The hypothesis test obtained a calculated t value> t table or (7.498> 1.990). Thus, H0 is rejected and Ha is accepted meaning there is a significant influence of compensation on employee performance. Work-life balance has a positive effect on employee performance with the regression equation value Y = 7.163 + 0.581 X2. The correlation coefficient is 0.793, meaning that the two variables have a strong relationship. The determination value is 62.9% while the remaining 37.1% is influenced by other factors. The hypothesis test obtained a calculated t value > t table or (11.644 > 1.990). Thus, H0 is rejected and Ha is accepted, meaning that there is a significant influence between work-life balance and employee performance. Compensation and work-life balance have a positive effect on employee performance simultaneously with the equation Y = 6.907 +0.065 X1 + 0.542 X2. The correlation coefficient value or the level of relationship between the independent variable and the dependent variable is obtained at 0.794, meaning that it has a strong relationship. The determination coefficient value simultaneously is 63.1% while the remaining 36.9% is influenced by other factors. The hypothesis test yielded a calculated F value > F table, or (67.476 > 3.112). Therefore, H0 is rejected and Ha is accepted. This means there is a significant simultaneous effect between compensation and work-life balance on employee performance.